2023
DOI: 10.3389/fendo.2023.1159127
|View full text |Cite
|
Sign up to set email alerts
|

Total serum FGF-21 levels positively relate to visceral adiposity differently from its functional intact form

Abstract: ObjectiveIncreased Fibroblast Growth Factor-21 (FGF-21) circulating levels have been described in obesity. In this observational study, we analysed a group of subjects with metabolic disorders to unravel the putative link between visceral adiposity and FGF-21 serum levels.MethodsTotal and intact serum FGF-21 concentration was measured with an ELISA assay respectively in 51 and 46 subjects, comparing FGF-21 levels in dysmetabolic conditions. We also tested Spearman’s correlations between FGF-21 serum levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…We previously identified increased visceral adipose tissue and oxidative stress as predisposing conditions to impaired reverse cholesterol transport (RCT), a process in which HDL particles are critically involved ( 33 ). In this study, HDL level intriguingly shows significant correlations with FPG and WC only in subjects with benign nodules, while a significant direct correlation with 25-OH vitamin D, as previously reported ( 34 , 35 ), was found only in patients with malignant nodules. On the one hand, the paradoxical uncoupling of cholesterol bioavailability and synthesis has already been shown in cancer cells ( 36 ).…”
Section: Discussionsupporting
confidence: 87%
“…We previously identified increased visceral adipose tissue and oxidative stress as predisposing conditions to impaired reverse cholesterol transport (RCT), a process in which HDL particles are critically involved ( 33 ). In this study, HDL level intriguingly shows significant correlations with FPG and WC only in subjects with benign nodules, while a significant direct correlation with 25-OH vitamin D, as previously reported ( 34 , 35 ), was found only in patients with malignant nodules. On the one hand, the paradoxical uncoupling of cholesterol bioavailability and synthesis has already been shown in cancer cells ( 36 ).…”
Section: Discussionsupporting
confidence: 87%
“…Another marker is fibroblast growth factor 21 (FGF-21). In fact, data generated from both adult and pediatric cohorts demonstrated that the circulating FGF-21 levels were positively correlated with NAFLD and NASH [ 30 ].…”
mentioning
confidence: 99%